QUALITY CONTROL ANALYSIS TO MINIMIZE THE NUMBER OF DEFECTS IN RATTAN CHAIRS USING THE SIX SIGMA METHOD - Syarifatul Annisa; Dwi Retna Sulistyawati (Science and Technology (SciTech), 2024)
PT XYZ is a company in the furniture industry. PT XYZ strives to maintain and improve the quality of their products in order to complete in the global market. Therefore, this research was conducted to find and analyze the company’s quality control process to identify the main causes of decreased product quality. This research uses six sigma with the Define, Measure, Analyze, Improve (DMAI) approach. The purpose of this research is to determine the factors that cause product quality, and determine improvements that can be made to improve the quality of rattan chair products. This research results showed that there were 4 types of defects that occured, namely defective wood with a percentage of 36%, untidy finishing with a percentage of 41%, untidy rattan with a percentage of 10% and cracked wood with a percentage of 13%. From the results of data processing at the measurement stage, the DPMO value was 56250,00 with a sigma level of 3,13, which means six sigma perfomance is equivalent to 93,32%. In this way, the company is expected to continue to make improvements and improve quality.